2009
DOI: 10.1161/circulationaha.108.840603
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Five-Year Outcome of Pediatric Coronary Artery Bypass Surgery for Kawasaki Disease

Abstract: Background-The long-term outcome of pediatric coronary artery bypass for patients with severe inflammatory coronary sequelae secondary to Kawasaki disease is unknown. Methods and Results-One hundred fourteen children and adolescents ranging in age from 1 to 19 (median, 10) years at operation were followed up for as long as 25 years with a median of 19 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
119
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(127 citation statements)
references
References 33 publications
1
119
0
7
Order By: Relevance
“…50 The incidence of ITA reopening is unknown, however, in our series of CABG operations for Kawasaki disease in which angiographic evaluation was repeated more than 3 or 4 times from 1 month until later than 20 years after the operation; 18 (12%) of the 154 ITA grafts were judged as occluded early after the operation, most likely due to flow competition between the graft and the less stenotic coronary artery with aneurysmal dilation. At repeat angiography, 4 (22%) of these were found to be functioning in the late (3-5 years) postoperative period, with a resultant improvement of the ITA graft patency rate from 88% to 39 Late ITA recanalization was not rare, although the patient group in that study consisted of pediatric patients, so further studies will be needed to determine whether this is also true of adult patients. The sequence of the string phenomenon of arterial grafts is shown in Figure 1.…”
Section: Progression Of Coronary Artery Obstructive Diseasementioning
confidence: 96%
See 1 more Smart Citation
“…50 The incidence of ITA reopening is unknown, however, in our series of CABG operations for Kawasaki disease in which angiographic evaluation was repeated more than 3 or 4 times from 1 month until later than 20 years after the operation; 18 (12%) of the 154 ITA grafts were judged as occluded early after the operation, most likely due to flow competition between the graft and the less stenotic coronary artery with aneurysmal dilation. At repeat angiography, 4 (22%) of these were found to be functioning in the late (3-5 years) postoperative period, with a resultant improvement of the ITA graft patency rate from 88% to 39 Late ITA recanalization was not rare, although the patient group in that study consisted of pediatric patients, so further studies will be needed to determine whether this is also true of adult patients. The sequence of the string phenomenon of arterial grafts is shown in Figure 1.…”
Section: Progression Of Coronary Artery Obstructive Diseasementioning
confidence: 96%
“…This is apparently the reason why the ITA graft remains patent and morphologically stable for a long duration after surgery, whereas the SVG tends to develop local narrowing with intimal hyperplasia and degenerative dilation, and eventually, atherosclerosis. 39 The ITA undergoes adaptive enlargement of its lumen in response to increased flow demand, as well as remodeling in response to decreased flow demand, resulting in a string-like shrinkage, both of which are endothelium-dependent phenomena. In 1992, my group first established a correlation between the ultimate ITA luminal diameter and the severity of proximal coronary stenosis following CABG.…”
Section: Progression Of Coronary Artery Obstructive Diseasementioning
confidence: 99%
“…216 a. Graft Patency The patency of internal thoracic artery grafts, that are the only available grafts for CABG in children, is as high as 87% overall, and 91%, 100%, and 84% when grafted to the left anterior descending artery, the left circumflex artery, and the right coronary artery, respectively, at 20 years after CABG. 217 …”
Section: Outcome Of Surgerymentioning
confidence: 99%
“…Involvement of the graft vessel from the episode of KD is very unlikely. Kitamura et al 5 have shown that bypass grafting can be performed in pediatric patients as young as 1 year of age, with no operative or hospital deaths, and a 25-year patient survival rate of 95%. Cardiac event-free survival at 25 years was 60%, with the majority of events being PCI or reoperation.…”
Section: Article See P 60mentioning
confidence: 99%